Застосування темпоральної логіки при побудові формальних моделей електронних текстів - Вавіленкова, Анастасія Ігорівна (НТУ "ХПІ", 2017)
Змістовний аналіз електронних текстових документів передбачає виявлення та встановлення логічних зв’язків між формальними моделями, якими описується зміст окремих частин – речень природної мови. Тому у статті проаналізовано засоби опису впорядкованості подій у часі, що базуються на темпоральній логіці, та запропоновано формальні правила та шаблони для автоматичного визначення часових рамок електронного текстового документу за рахунок відстеження ланцюжків тем і рем, тобто послідовності розгортання думки.

The content analysis of electronic text documents involves identifying and establishing of logical links between formal models that describe the content of separate parts - the natural language sentences. Therefore, the purpose of the article is to develop formal rules and templates for the automatic determination of the time frame of an electronic text document by tracking themes and rhymes, that is, the sequence of unfolding ( deployment) of thought. The study analyzes the existing means of setting the time frame in text documents based on temporal logic: first, to analyze the means of unfolding of thought in a text document, then to form the formal rules and templates to identify the thematic progress in electronic text documents. It is provided a geometric interpretation of three variants for template construction: for sequential unfolding of thought in the text, for one topic, which is repeated in each sentence of the text, and for the split topic. Unfolding thoughts in texts can take place in different ways, so the proposed rules and templates can be combined. If the constructed array of logic and linguistic models for the text fragment coincide with one of the types of the indicated templates, then it will be possible to automatically determine the nature of the unfolding of thought in this fragment. The article demonstrates an example of constructing one of the proposed templates for a text fragment. To Formulated formal conditions and developed templates are the basis for establishing content links in electronic text documents in general.
Application of temporal logic for construction of formal models of electronic texts
Keywords: логіко-лінгвістична модель; природна мова; зміст; змістовний аналіз; natural language; temporal logic